2023
DOI: 10.5530/ijpi.14.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Future Prospects: A Benefaction of Phytoconstituents on Molecular Targets Pertaining to Alzheimer’s Disease

Himanshu Sharma,
Phool Chandra

Abstract: Background: Many parts of the brain experience excruciating pain as a result of Alzheimer's disease, a form of dementia. Cognitive processes and neuropsychiatric regulation are disrupted by the numerous neuropathologies that exist. The everyday activities, social and professional lives, and overall health of the individual are all substantially impacted by this ongoing deterioration. In this, we comprehend the advantages and practicality of phytoconstituents on the molecular targets of Alzheimer's disease. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…They suggested that its use has promising effects regarding neuronal impairments. Other authors have shown BM constituents' effects as benefits in dementia, Alzheimer´s disease, and other brain disorders [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that its use has promising effects regarding neuronal impairments. Other authors have shown BM constituents' effects as benefits in dementia, Alzheimer´s disease, and other brain disorders [42][43][44].…”
Section: Introductionmentioning
confidence: 99%